Status of teaching and learning descriptive writing in Zanzibar secondary schools: a case of Wete District - Hamad, Ali Juma; Ndibalema, Placidius; Matalu, Kulwa (Universitas Majalengka, 2024)
This paper investigated the status of teaching and learning descriptive writing among Secondary Schools in Zanzibar. The paper focused on (i) Identifying the types of errors made by secondary school students in their descriptive writing skills and (ii) exploring teaching and learning materials in descriptive writing for secondary schools. A mixed method approach was used, and a case study design employed. Simple random sampling was used to select 140 form four students and they have given a test. Also, eight English language subject teachers and two quality assurers were purposively selected. Data were collected using students’ test, interview, and documentary reviews. The results depict that students had different errors such as grammatical errors, punctuation marks, coherence and content problems. Also, the findings show that many topics prosed using non-digital materials such as textbooks, and written text for teaching and learning descriptive writing in secondary schools. These materials were also not sufficient to give students ability and competence in descriptive writing in ordinary secondary schools. This indicates that there is a need for designing digital lessons for supporting teaching and learning descriptive writing for F1 students. The study concludes that proper teaching and learning digital contents lessons is needed to support teachers and motivate students in the teaching and learning of descriptive writing to secondary school students. To achieve effective descriptive writing to secondary school students, curriculum developers, teachers and other education stakeholders should emphasize on digital materials to motivate students in teaching and learning process.